Effects of Hyperbaric Oxygen Therapy Combined with Music Therapy on Brain Function and Mental Health of Patients with Aneurismal Subarachnoid Hemorrhage: A Retrospective Study - Xiaoliang Wu; Shengli Zhang; Lihong Ma; Na Wang; Wei Song (Noise and Health)
Background: Hyperbaric oxygen therapy (HBOT), which is widely used in clinical practice, is aimed at improving nerve function impairment after brain injury. Meanwhile, the effects of music therapy on brain function are unclear. This retrospective study was conducted to explore the application effect of HBOT combined with music therapy on patients suffering from aneurysmal subarachnoid hemorrhage (aSAH). Methods: For this retrospective study, 130 patients with aSAH after HBOT were selected from our hospital from June 2021 to June 2022. The patients were divided into the observation (n = 70) and control (n = 60) groups based on whether they received music therapy. Comparisons were made on general demographic data, blood flow rate in median cerebral artery (MCA), cerebral vasospasm (CVS), National Institutes of Health Stroke Scale (NIHSS), activities of daily living (ADL) score, Self-Rating Depressive Scale (SDS), and Self-Rating Anxiety Scale (SAS) of patients. Results: Baseline data between the two groups showed no statistically significant difference (P > 0.05). After management, patients in the observation group presented significantly lower SAS and SDS scores (P < 0.05), lower blood flow rate in MCA, CVS and NIHSS scores (P < 0.05), and higher ADL scores than the control group (P < 0.05). Conclusions: The combination of HBOT and music therapy can considerably improve cerebral neurological deficits, slow down cerebral arterial blood flow, promote the recovery of postoperative cerebral function in aSAH patients, and improve anxiety and depression and the patients’ ADL.